If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 + -3 = 12x + -1(8x + -4) Reorder the terms: 1 + -3 + 6x = 12x + -1(8x + -4) Combine like terms: 1 + -3 = -2 -2 + 6x = 12x + -1(8x + -4) Reorder the terms: -2 + 6x = 12x + -1(-4 + 8x) -2 + 6x = 12x + (-4 * -1 + 8x * -1) -2 + 6x = 12x + (4 + -8x) Reorder the terms: -2 + 6x = 4 + 12x + -8x Combine like terms: 12x + -8x = 4x -2 + 6x = 4 + 4x Solving -2 + 6x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 6x + -4x = 4 + 4x + -4x Combine like terms: 6x + -4x = 2x -2 + 2x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + 2x = 4 + 0 -2 + 2x = 4 Add '2' to each side of the equation. -2 + 2 + 2x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 4 + 2 2x = 4 + 2 Combine like terms: 4 + 2 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| -56+-1x+x^2=0 | | 6y^2+29y=22 | | (z+7)(z-8)=0 | | 4x^2-64x-68=0 | | 2(3+2x)-2=20 | | 24y-14y=5 | | 4z-3(2+1)=2(z-3)-z | | (x-4)(x-6)=-21 | | -13+(-4)(-2)= | | w^2-8w=20 | | 29x^2-7=0 | | .02(2c-24)=-0.4(c-1) | | 5a+3(8-a)=36 | | -97=-6x+11 | | (x+4)(x+6)+21=0 | | (x+4)(x+6)=-21 | | x+2=3-2x+8 | | -4c+4+2c=3c-16 | | 10x^2-3x-13=0 | | -m+1=14 | | 12b^4+3b= | | 2+3y-4=5y+6 | | 4x^2=2+2x | | 3x+2-5x=-x+3 | | x^2+2x-195=0 | | (4u+2)(7-u)=0 | | -8p-5=91 | | 32=8+6b | | 10n=20 | | -5-11=14 | | 54(15)=15(75)+3(2)(d) | | 9=3k+9 |